Developing a Transitions of Care Elective for Medical Students during the COVID-19 Pandemic and Beyond. Issue 8 (August 2021) - Salib, Sherine; Amadin, Abi; Brode, W. Michael; Johnston, Clarissa; Patel, Snehal; Pignone, Michael
Abstract: Objectives: Health care in the United States is costly, fragmented, and often ineffective. Transitions of care (TOC), particularly from the inpatient to the outpatient setting, is an especially complicated time and one that is potentially fraught with errors that contribute to negative outcomes. The coronavirus 2019 pandemic exacerbated many of these challenges. In particular, vulnerable patient populations have experienced more barriers to successful care transitions. Effective care transitions should include interprofessional teamwork, robust patient education, and seamless communication among the various healthcare team members. Increasingly, medical schools are working toward graduating systems-ready physicians who demonstrate competency in the health system sciences and are able to operate effectively within the healthcare system, including being able to navigate complex transitions of care issues. Undergraduate medical education, however, continues to provide experiential learning in the traditional silos of inpatient versus outpatient medicine, so that learners do not have the opportunity to directly participate in transitions of care. Although transitions of care is a pivotal part of patient care, it is rarely taught at the undergraduate level, and when it is, it is typically relegated to the classroom setting. Methods: We used the disruption of the coronavirus 2019 pandemic to develop a TOC elective. The aim was to fulfill an acute educational need and to develop competencies around care transitions for students while concurrently providing support for patient care and teamwork. The elective was offered to second-, third- and fourth-year medical students. Our educational innovation was initiated within our safety-net hospital where we care for a high percentage of uninsured patients, with a high language discordance. In addition, our city has multiple care systems without a single or connected electronic health record system, further complicating patient care transitions. The work of the TOC elective crossed inpatient and outpatient silos, with close collaboration with our local federally qualified health centers. This remotely conducted elective includes three main pillars: participation in team activities, including virtual participation in interdisciplinary rounds and care coordination; discharge planning; and communication, including goals of care and end of life communication. Results: Medical students successfully integrated into team structures to directly counsel families, facilitate goals of care conversations, and engage a multidisciplinary team for discharge planning. Students found this experience valuable in their reflections. In addition, there was a value-added component from a patient care and teamwork perspective. Conclusions: Participation of students in TOC is a valuable educational experience and contributes a value-added component to patient care and interprofessional teamwork. Moreover, an appreciation of the failures of the current system is pivotal as learners start to reimagine, explore, and design improved patient-centered systems in the future. Abstract : Transitions of care is one of the most complex, and often one of the most problematic, aspects of healthcare systems, leading to errors and negative outcomes when not done effectively. Transitions of care, however, is rarely taught in undergraduate medical education, and when it is, it is typically relegated to the classroom setting. The authors describe a new elective experience that not only holds educational value for students but also entails a value-added component for patient care and teamwork.